Market Delivery Model untuk Cost Efficiency terhadap Customer Satisfaction in Logistics di Indonesia: Tinjauan Literatur - Adhanti Eka Fitriyani; Eliyanti Agus Mokodompit (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
This study examines market delivery models in the context of maritime logistics in Indonesia, focusing on cost efficiency and customer satisfaction. Indonesia faces significant challenges in market delivery models, primarily due to the disparity in costs and service time between the western and eastern regions. This inefficiency is largely caused by the dependence on sea transport for inter-island logistics, high dwelling time at ports, and cargo flow imbalance. Although the sea toll program has improved connectivity, these fundamental issues still hinder cost efficiency. Maritime logistics has a significant indirect impact on customer satisfaction, where delays and cargo damage trigger consumer dissatisfaction. This literature review utilizes the Systematic Literature Review (SLR) method, analyzing relevant articles from various sources such as Google Scholar, Semantic Scholar, Elsevier, and other online journal publications. The focus of the study is the relationship between maritime operations (ports, vessels) with costs and service quality. The results indicate that an efficient delivery model must integrate solutions such as the use of Third-Party Logistics (3PL) for freight consolidation, decentralized fulfillment strategies with regional hubs, and cargo flow optimization to reduce rates. Additionally, port digitalization through the implementation of Port Information Systems (SIPP) and electronic document exchange has been shown to reduce cargo processing times and dwelling time, directly improving cost efficiency and customer satisfaction.